GEOLOGY OF LAHAT – MENGLEMBU AREA WITH EMPHASIS ON ROCK STRENGTH PARAMETERS - SANTHA MOORTHY, PRIVEEN RAJ (Universiti Teknologi PETRONAS, 2015)
This paper reviews the present state knowledge of Lahat and Menglembu area and aims to identify deformations in the rocks and to propose a regional structural history of Kledang Range. The dominant lithology observed in this study is syenogranite which is later overlain by a thick blanket of alluvium. The thick blanket alluvium is a result of weathering process of the syenogranite itself. While for the structural analysis of Lahat and Menglembu, it is observed that, both the outcrops are dominated by normal and dextral strike slip faults. While the occurrence of the blocky and wedged block is due to different orientation of jointing pattern and due to exfoliation fracture respectively. The results obtained from satellite imagery, regional scale observation and field observation shows that, the faulting pattern is mainly aligned towards NNW-SSE, ENE-WSW and NE-SW suggesting a roughly E-W compression force. From the triaxial test conducted both on Lahat and Menglembu granite, it is observed that, Lahat granite displays slightly higher rock strength compare to Menglembu granite. This is mainly because of the grain size and the mineral content of Lahat granite compared to Menglembu granite.